Neurodynamic Technique on Functional Ankle Instability: A Case - Ramalingam, Vinodhkumar; Sundar, Viswanath; Joseph, Saju (2018)
Athletes who encountered repeated Functional Ankle Instability (FAI), exhibit excessive foot inversion during the various phases of gait than non-injured ankle. In gait, heel strike to toe off inversion ankle movement of the foot is controlled by eccentric function of the peroneus muscle, which stabilizes the ankle joint. As such, the purpose of this study was to investigate the response of biomechanical characteristics during gait cycle by applying neurodynamic exercise technique. An athlete with repeated FAI was checked for dynamic balance (Y-balance) and knee range of motion (using a electro-goniometer). To test the peroneal longus muscle activity and gait parameters synchronisation of Surface Electromyography (sEMG) (Noraxon Myo-Muscle) was done with an instrumented myo-pressure treadmill in both injured and non-injured legs. Six-week post intervention measurements exhibited significant improvement in dynamic balance, knee range of motion, pain score, efficient peroneal muscle response and gait parameters. This ascertains the effect of neurodynamic technique